Improvement of the In Vitro Cytotoxic Effect on HT-29 Colon Cancer Cells by Combining 5-Fluorouacil and Fluphenazine with Green, Red or Brown Propolis - Falcão, Soraia I.; Duarte, Diana; Diallo, Moustapha; Santos, Joana; Ribeiro, Eduarda; Vale, Nuno; Vilas-Boas, Miguel (Molecules, 2023)
Cancer is regard as one of the key factors of mortality and morbidity in the world. Treatment is mainly based on chemotherapeutic drugs that, when used in targeted therapies, have serious side effects. 5-fluorouracil (5-FU) is a drug commonly used against colorectal cancer (CRC), despite its side effects. Combination of this compound with natural products is a promising source in cancer treatment research. In recent years, propolis has become the subject of intense pharmacological and chemical studies linked to its diverse biological properties. With a complex composition rich in phenolic compounds, propolis is described as showing positive or synergistic interactions with several chemotherapeutic drugs. The present work evaluated the in vitro cytotoxic activity of the most representative propolis types, such as green, red and brown propolis, in combination with chemotherapeutic or CNS drugs on HT-29 colon cancer cell lines. The phenolic composition of the propolis samples was evaluated by LC-DAD-ESI/MSn analysis. According to the type of propolis, the composition varied; green propolis was rich in terpenic phenolic acids and red propolis in polyprenylated benzophenones and isoflavonoids, while brown propolis was composed mainly of flavonoids and phenylpropanoids. Generally, for all propolis types, the results demonstrated that combing propolis with 5-FU and fluphenazine successfully enhances the in vitro cytotoxic activity. For green propolis, the combination demonstrated an enhancement of the in vitro cytotoxic effect compared to green propolis alone, at all concentrations, while for brown propolis, the combination in the concentration of 100 μg/mL gave a lower number of viable cells, even when compared with 5-FU or fluphenazine alone. The same was observed for the red propolis combination, but with a higher reduction in cell viability. The combination index, calculated based on the Chou–Talalay method, suggested that the combination of 5-FU and propolis extracts had a synergic growth inhibitory effect in HT-29 cells, while with fluphenazine, only green and red propolis, at a concentration of 100 μg/mL, presented synergism.